Implementasi Model Pembelajaran Kooperatif Tipe Jigsaw Dalam Meningkatkan Partisipasi Aktif Siswa Kelas XII Pada Mata Pelajaran Al-Qur’an Hadits di MAN 1 Banyumas - Nurrohmah, Icha; Intan Pandini , Yosi (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Education serves as a fundamental pillar in developing quality human resources, both intellectually and spiritually. In the context of Islamic religious education, students’ active participation is a crucial factor in achieving a deep understanding of the values contained in the Qur’an and Hadith. This study aims to describe the implementation of the Jigsaw cooperative learning model in enhancing the active participation of Grade XII students in the Al-Qur’an Hadith subject at MAN 1 Banyumas. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects included Grade XII students, the Al-Qur’an Hadith teacher, and the school principal. The findings indicate that the teacher’s modified Jigsaw model effectively increased students’ active participation through three main stages: planning, implementation, and evaluation.Moreover, students developed communication skills, teamwork, and critical thinking. The study concludes that a contextually modified Jigsaw model can serve as an effective instructional strategy for the Al-Qur’an Hadith subject. Recommendations are offered for teachers, students, future researchers, and school administrators for further improvement and development.